FAKTOR SOSIAL DALAM PERUBAHAN BAHASA PADA GRUP FACEBOOK JUAL BELI HP BEKAS SE-SOLO RAYA - Habib Salim Al Khoir; Devanni Kusuma Putri (Translation and Linguistics (Transling), 2024)
This study aims to look for the social factors influencing language changes in bergaining second-hand cellphones on Facebook groups in Solo Raya. This research is a qualitative descriptive research using note-taking technique as the data collection technique. The research source is located in a Facebook group when bergaining activities for second hand cellphones in Solo Raya happened. The source of data and data in this study used purposive sampling technique. This group was chosen as the data source because it is a platform for people to gather with others in various social backgrounds. Therefore, these people have a special language that is used in bergaining activities that influences language in terms of form and meaning. The results of this study indicate that the language used in bergaining second-hand cellphone activities on this facebook group is influenced by three factors, namely: (1) education level, (2) age factors, (3) social class. The level education factors influences the spelling of a word because people tend to make it easier to write the foreign words. Besides, the age factors influences the shift of word meaning. Meanwhile, the social class factors make them using krama inggil and madya language to show honor and respect other members.